1996
DOI: 10.1016/s0092-8674(00)81305-7
|View full text |Cite
|
Sign up to set email alerts
|

Tertiary Structure of Destrin and Structural Similarity between Two Actin-Regulating Protein Families

Abstract: Destrin is an isoprotein of cofilin that regulates actin cytoskeleton in various eukaryotes. We determined the tertiary structure of destrin by triple-resonance multidimensional nuclear magnetic resonance. In spite of there being no significant amino acid sequence homology, we found that the folding of destrin was strikingly similar to that of repeated segments in the gelsolin family, which resulted in a new protein fold group. Sequential dissimilarity of the actin-binding helix of destrin to that of gelsolin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
133
0
2

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(139 citation statements)
references
References 66 publications
4
133
0
2
Order By: Relevance
“…Both mutant proteins inhibit the assembly and disassembly of actin as compared with maize ADF3. These data are discussed in relation to the tertiary structures of destrin (32) and yeast cofilin (33).…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…Both mutant proteins inhibit the assembly and disassembly of actin as compared with maize ADF3. These data are discussed in relation to the tertiary structures of destrin (32) and yeast cofilin (33).…”
mentioning
confidence: 96%
“…Phosphorylation inhibits interaction with actin, whereas dephosphorylation promotes interaction. Under certain conditions, cofilin and actin form intranuclear cofilin:actin rods and a nuclear localization signal has been identified between Lys-19 and Lys-34 (32,35,36). Cofilin is dephosphorylated prior to translocation into the nucleus.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…) family, is a possible source for the single-domain gene that was duplicated to form the multi-domain actin-severing proteins (Hofmann et al, 1993). Comparison of the sequences of destrin and villin 14T, aligned by structural elements (Hatanaka et al, 1996) and allowing conservative replacements in the sets (R, K), (V, I, L, F, Y, W, H), and (E, Q), shows that the sequence similarity is about 21 %, consistent with the similarity in the fold. Two of the proposed calcium binding ligands for villin 14T are not conserved in destrin, consistent with destrin's calcium-independent affinity for actin.…”
Section: Comparison With the Actin-regulating Protein Destrinmentioning
confidence: 70%
“…The structure of severin domain 2 in solution is also available (Schnuchel et al, 1995). These studies have revealed that the conserved repeated domain has a unique fold, comprised of both /?-sheet and a-helix, observed so far only in the actin-severing proteins and the single-domain actin regulating protein destrin (Hatanaka et al, 1996). Many of the residues within the most strongly conserved region contribute to the hydrophobic core of the molecule and to the turns between elements of secondary structure and thus are conserved for structural rather than functional reasons.…”
mentioning
confidence: 99%